Combined Strengthening of Batan Teeth of the Stb Loom - Kasimov Bakhtiyor Murat o’g’li; Muminov Mansur Rakhimovich; Shin Ilarion Georgievich (International Journal on Orange Technologies, 2021)
The combined strengthening of the batan teeth of the STB loom is considered, including chemical and thermal treatment-nitrocementation and surface plastic deformation in the form of shot blasting. Shot hardening forms compressive residual stresses in the surface layer, which, together with the increased hardness, increases the wear resistance of the batan teeth.